Profundidades de coleta de solo para fins de levantamento pedológico no estado do Ceará: um diagnóstico crítico - Geremias, Manuel (2020)
The soil survey consists of determining from a description of the characteristics related to the soil properties, predicting, and delineating their areas on the maps through soil classes. For the soil survey to be carried out, it is essential to have knowledge about its formation, genesis and morphology of the environment where it develops and about the changes that may eventually occur as a result of its use. Bearing in mind that the evolution of soils occurs from the weathering process, that is, the transformation of rocks present on the planet's surface from its beginning, through the factors of soil formation (weather, climate, relief, organism and source material), the arrangement between them in a given region is what defines the different types of horizons and consequently types of soils existing in the world, such as the different ways of collecting them. From this, the objective of this work was to analyze the depths of soil collection that already exist, in addition to enabling a new proposal due to an analysis carried out at different depths. For this, the survey of soil profile information in the materials was carried out, which contains all the information of the soil profiles collected until the present day in the state of Ceará. Data was planned in the Microsoft Excel program, statistically analyzing the information, to identify the occurrence of superficial and subsurface horizons in relation to depth. The results showed that at depths 0-15, 15-35, 40-55 and 60-75cm it is possible to identify the type of soil from the characteristics of the genesis of regional soils, as it is in these depths where there was a greater occurrence of horizons, ensuring better results in chemical and physical analysis in the laboratory, and consequently, facilitating the interpretation of data in relation to superficial or subsurface horizons. However, the depths of 0-20; 40-60, 80-100 currently proposed by the survey are not representative for the state of Ceará.